Dossier: “Public Policies for Territorial Development in Latin America” - Sabourin, Eric; Sayago, Doris (Sustainability in Debate, 2013)
This dossier is devoted to the subject “Public Policies for Territorial Development in Latin America”. It is true that articles about either public policies for rural development or territorial and environmental development have already been published in Sustainability in Debate. However, this present dossier has the merit of introducing scientific articles that combine both research subjects ”“ public policies for rural and for territorial/environmental development.